2022
DOI: 10.1177/08902070221080278
|View full text |Cite
|
Sign up to set email alerts
|

Whose self-control development suffers or benefits in the face of adversity? A longitudinal study of Mexican-origin youth followed from age 10 to 16

Abstract: This study assessed the co-development of adversity and effortful control based on a sample of Mexican-origin youth ( N = 674) and their parents. We used a four-wave longitudinal design and followed target participants from age 10 to 16. At each time point, we measured adversity experienced by the children and their parents and children’s effortful control (self- and parent-reported). We also assessed children’s shift-and-persist coping strategies at ages 14 and 16. Across time, we found slight decreases in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…Our findings align with prior research that showed stability in a variety of outcomes following an event ( Milojev et al, 2014 ; Chopik et al, 2021 , 2022 ; Blackie and McLean, 2022 ; Fassbender et al, 2022 ; Forgeard et al, 2022 ; Jayawickreme et al, 2022 ; Reitz et al, 2022 ) and thus provide further evidence that stability in well-being is the more typical response to major life events (e.g., Infurna et al, 2022 ; Laceulle et al, 2022 ; Serrano et al, 2022 ). Furthermore, in line with growing longitudinal evidence, our results fail to detect evidence for possible post-traumatic growth following major life stressors, insofar as such growth might relate to a broad range of different aspects of well-being ( Davis et al, 2021 ; Rakhshani and Furr, 2021 ; Dorfman et al, 2022 ; Infurna et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings align with prior research that showed stability in a variety of outcomes following an event ( Milojev et al, 2014 ; Chopik et al, 2021 , 2022 ; Blackie and McLean, 2022 ; Fassbender et al, 2022 ; Forgeard et al, 2022 ; Jayawickreme et al, 2022 ; Reitz et al, 2022 ) and thus provide further evidence that stability in well-being is the more typical response to major life events (e.g., Infurna et al, 2022 ; Laceulle et al, 2022 ; Serrano et al, 2022 ). Furthermore, in line with growing longitudinal evidence, our results fail to detect evidence for possible post-traumatic growth following major life stressors, insofar as such growth might relate to a broad range of different aspects of well-being ( Davis et al, 2021 ; Rakhshani and Furr, 2021 ; Dorfman et al, 2022 ; Infurna et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…Such studies show remarkable stability pre-and post-event across a range of outcomes, including 10.3389/fpsyg.2022.1012120 empathy, life satisfaction, religiosity, and personality (Milojev et al, 2014;Chopik et al, 2021Chopik et al, , 2022Blackie and McLean, 2022;Dorfman et al, 2022;Fassbender et al, 2022;Forgeard et al, 2022;Jayawickreme et al, 2022;Reitz et al, 2022). Thus, stability or declines in functioning appear to be the more typical response to adversity, with growth or positive change being much less prevalent than suggested by prior cross-sectional research (Frazier et al, 2009;Davis et al, 2021;Rakhshani and Furr, 2021;Gander and Wagner, 2022;Infurna et al, 2022;Laceulle et al, 2022;Serrano et al, 2022). However, two primary shortcomings in current longitudinal research limit conclusions about growth or resilience.…”
Section: Introductionmentioning
confidence: 94%
“…Turning to another study of adversity within context, Serrano et al (2022) examined the impact of personal and parental adversity on the co-development of effortful control across 6-years in a sample of Mexican-origin adolescents. The results indicated that greater personal adversity experienced by adolescents was associated with decreases in the development of their effortful control, therefore providing evidence to the contrary of post-traumatic growth.…”
Section: A Personality Science Approach To the Study Of Post-traumati...mentioning
confidence: 99%
“…If higher AGC disrupts positive dyadic and familial dynamics (Smokowski et al, 2008), it may also inhibit familial and youth coping processes and, subsequently, youth functioning. Prior research found that shift-and-persist coping did not protect against the effects of parent acculturative stress on youth effortful control (Serrano et al, 2022). Research is needed in investigating other resilience processes that may intervene in the context of this family-based stressor.…”
Section: Discussionmentioning
confidence: 99%